The Clinical Spectrum of Mosaic Neurofibromatosis in Children and Adolescents. (March 2020) - Hom, Grant L.; Moodley, Sashidaran; Rothner, A. David; Moodley, Manikum
Background: Segmental neurofibromatosis was initially described by Miller and Sparks (1977) as manifestations of neurofibromatosis limited to a dermatomal, localized distribution. Now termed mosaic neurofibromatosis, previous literature described this disease in children and adolescents with individual case reports and small-numbered case series. This study presents a large series of children and adolescents with mosaic neurofibromatosis. Methods: A retrospective chart review of a single institution medical record database was performed on all cases of mosaic neurofibromatosis diagnosed between the years 1998 and 2017. Eligible subjects were determined by 2 criteria: (1) segmental or unilateral expression of one of more signs of NF I according to those outlined in the NIH criteria and (2) were under 18 years of age at the time of diagnosis. Select information extracted include location of clinical features, NF manifestations (neurofibromas, plexiform neurofibromas, café-au-lait spots, freckling, Lisch nodules), presence of a diffuse area of cutaneous hyperpigmentation, and other significant medical conditions. Results: Sixty-eight cases met established criteria. Average age at diagnosis was 8.28 ± 4.47 years. Thirty-seven (54%) were male and 31 (46%) were female. Localization of the dermatologic manifestations is as follows: left side in 28 (41%) cases, right side in 32 (47%) cases, and bilateral in 8 (11%) cases. Café-au-lait lesions appeared in 64 (94%) of cases and 14 (21%) had axillary and inguinal freckling. Conclusions: This study expands our understanding of the disease characteristics seen in children and adolescents with mosaic neurofibromatosis and confirms the need to focus on pigmentary changes in children with mosaic neurofibromatosis.